The impact of artificial intelligence on digital design processes: AI as a tool, not a replacement - Slobodina, Anastasiia; Kostikov, Mykola (My University, 2026)
Artificial intelligence (AI) is reshaping digital design by transforming workflows, accelerating ideation, and redefining the professional role of designers. Rather than replacing human creativity, AI operates as an augmentation system that enhances strategic and conceptual capacities. This paper critically examines AI-assisted design processes, evaluates their impact on authorship and creative agency, and identifies structural limitations of generative systems. The findings demonstrate that AI amplifies efficiency while preserving the irreplaceable role of human judgment, cultural awareness, and design ethics in contemporary digital practice. Штучний інтелект (ШІ) змінює цифровий дизайн, трансформуючи робочі процеси, прискорюючи генерування ідей та переосмислюючи професійну роль дизайнерів. Замість того, щоб замінити людську творчість, ШІ функціонує як система доповнення, яка покращує стратегічні та концептуальні можливості. У цій статті критично розглядаються процеси дизайну за допомогою ШІ, оцінюється їхній вплив на авторство та креативну діяльність, а також визначаються структурні обмеження генеративних систем. Результати дослідження демонструють, що ШІ підвищує ефективність, зберігаючи при цьому незамінну роль людського судження, культурної обізнаності та етики дизайну в сучасній цифровій практиці
Keywords: artificial intelligence; digital design; user experience; user interface; generative systems; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки; інтерфейс користувача; досвід користувача; штучний інтелект; цифровий дизайн